2017
DOI: 10.1111/1749-4877.12225
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory value of cracking‐clay soil shelters for small vertebrates during extreme desert conditions

Abstract: Deserts exhibit extreme climatic conditions. Small desert-dwelling vertebrates have physiological and behavioral adaptations to cope with these conditions, including the ability to seek shelter. We investigated the temperature (T) and relative humidity (RH) regulating properties of the soil cracks that characterize the extensive cracking-clay landscapes of arid Australia, and the extent of their use by 2 small marsupial species: fat-tailed and stripe-faced dunnarts (Sminthopsis crassicaudata and Sminthopsis ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…In addition, our findings support that more heterogeneous environments can reduce the costs for thermoregulation in animals (Basson et al, 2017;Ryeland et al, 2021). Importantly, microtopographic features, such as boulders (Shi et al, 2014) and cracks in the soil (Waudby & Petit, 2017), have been shown to provide insulation from extreme temperatures. Therefore, future studies should investigate whether microclimates created by beach-cast wrack assist thermoregulation in shorebirds during extreme heat events, which are increasing in our study area due to climate change (Braganza et al, 2013).…”
Section: Conservation Management Implicationssupporting
confidence: 73%
“…In addition, our findings support that more heterogeneous environments can reduce the costs for thermoregulation in animals (Basson et al, 2017;Ryeland et al, 2021). Importantly, microtopographic features, such as boulders (Shi et al, 2014) and cracks in the soil (Waudby & Petit, 2017), have been shown to provide insulation from extreme temperatures. Therefore, future studies should investigate whether microclimates created by beach-cast wrack assist thermoregulation in shorebirds during extreme heat events, which are increasing in our study area due to climate change (Braganza et al, 2013).…”
Section: Conservation Management Implicationssupporting
confidence: 73%
“…These preferences are consistent with published information on habitat use in each species (e.g. Dickman et al ; Haythornthwaite ; van Dyck & Strahan ; Pavey et al ; Waudby & Petit ; Molyneux et al ).…”
Section: Discussionsupporting
confidence: 90%
“…However, these Scott Creek data show very small standard errors. Such small standard errors also appear in Keppel et al (2017) for grass-trees in summer and Waudby and Petit (2017) for soil cracks in summer, indicating that similar shade types are associated with similar temperatures in the same environment at the same time. We are thus confident that means are fair representations of temperatures.…”
Section: Temperature Under the Canopy Of Grass-treesmentioning
confidence: 87%